Present Bias in Politics and Self-Committing Treaties - Bård Harstad; Anke Kessler (CESifo GmbH, 2025)
We study how international environmental agreements can take advantage of domestic time-inconsistency problems. Policymakers often prefer future policies to be sustainable, but are tempted to invest less when being in office. We find the equilibrium number of signatory countries to be higher than when preferences are time consistent, especially when the political environment is unstable and polarized and the international spillovers are limited. This model also explains participation in treaties whose mandates do not vary with the coalition size and why the coalition will not unravel if, for example, the US exits the Paris Agreement.
Keywords: Q54; Q58; H87; F53; 330; international treaties; time inconsistency; self-commitment; environmental policy